Determinación del costo de producción de tres platos tipicos servidos en el restaurant asadero “don Hugo” de la ciudad de Quito, periodo: marzo 2015 - Carrión Ramón, Mayra Jimena (2016)
This paper titled “Determining the cost of production of three dishes served at the Restaurant “Asadero Don Hugo” of Quito, in the period of March 2015 period " , was conducted as a requirement of the National University of Loja , prior to graduation and obtaining the title of Engineer in Accounting and Auditing . CPA Accountant Auditor. For its development business information was compiled , which allowed for the entire accounting process, from the memorandum of operations until obtaining financial statements , in addition to that document formats control the cost elements was performed. It met the objectives: 1- Get an estimate of the indirect costs to apply the default rate according to production business. 2 - Make the subsidiary records to assist the registration and control of cost elements. 3- Determine the unit cost of products made in recognition of the raw material, labor and manufacturing overhead costs.